The Influence of Affiliate Marketing Strategies on Increasing Sales on E-commerce Platforms - Indah Maulida; Agus Yudianto; Meddy Nurpratama; Nana Supriatna Sonjaya (Business, Accounting, and Knowledge Journal, 2025)
This research aims to determine the effect of affiliate marketing strategies on increasing sales on the E-commerce platform. The object of research is Wiralodra University students. The population of the sampling technique was 70 students. The data analysis technique in this study used simple regression. The results of the Pearson correlation value research between the Affiliate Marketing Variable and Increased Sales of 0.70, because the correlation value is in the range of 0.60 - 0.799, it can be concluded that the relationship between affiliate marketing and increased sales is Strong, which means that there is a positive relationship. positive and significant effect on increased sales.